FENOMENA CYBERSEX DITINJAU DARI SUDUT PANDANG KRIMINOLOGI - Gabriella Monica Muaya (2023)
The more advanced and modern society is, the more crime types and modes occur. One of the negative impacts is that the internet or cyberspace has become a means for committing various acts of crime and violence online, known as cybercrime. One of the cybercrime phenomena that raises concerns that continues to grow and is known among modern people worldwide is cybersex. Cybersex has been included in the OSA (Online Sexual Activity) category, where the internet is used to fulfill sexual desires. Thus, cybersex can be interpreted as an activity that aims to satisfy individual sexual needs, such as viewing erotic images, chatting about matters related to sexuality, and doing cybering through internet media. The purpose of this study is to find out and analyze the factors that cause cybersex and also to find out and explain law enforcement against perpetrators of cybersex crimes. The research method used in this study is a normative juridical research method. The factors that cause the cybersex phenomenon are legal awareness factors, legal structure factors, legal substance factors, legal culture factors, and environmental factors. Law enforcement regarding cybersex crimes is not only limited to one law, but several laws that have been passed do not regulate cybersex. Therefore, strong regulations are needed to control and provide firm legitimacy for cybersex perpetrators to realize this law enforcement optimally.